TMCO1 deficiency causes autosomal recessive cerebrofaciothoracic dysplasia. Issue 2 (5th November 2013) - Alanay, Yasemin; Ergüner, Bekir; Utine, Eda; Haçarız, Orçun; Kiper, Pelin Ozlem Simsek; Taşkıran, Ekim Zihni; Perçin, Ferda; Uz, Elif; Sağıroğlu, Mahmut Şamil; Yuksel, Bayram; Boduroglu, Koray; Akarsu, Nurten Ayse
Abstract Cerebrofaciothoracic dysplasia (CFT) (OMIM #213980) is a multiple congenital anomaly and intellectual disability syndrome involving the cranium, face, and thorax. The characteristic features are cranial involvement with macrocrania at birth, brachycephaly, various CT/MRI findings including hypoplasia of corpus callosum, enlargement of septum pellicidum, and diffuse hypodensity of the grey matter, flat face, hypertelorism, cleft lip and cleft palate, low‐set, posteriorly rotated ears, short neck, and multiple costal and vertebral anomalies. The underlying genetic defect remains unknown. Using combination of homozygosity mapping and whole‐exome sequencing, we identified a homozygous nonsense founder mutation, p.Arg87Ter (c.259 C>T), in the human transmembrane and coiled‐coil domains protein 1 (TMCO1) in four out of five families of Turkish origin. The entire critical region on chromosome 1q24 containing TMCO1 was excluded in the fifth family with characteristic findings of CFT providing evidence for genetic heterogeneity of CFT spectrum. Another founder TMCO1 mutation has recently been reported to cause a unique genetic condition, TMCO1‐defect syndrome (OMIM #614132). TMCO1‐defect syndrome shares many features with CFT. This study supports the fact that "TMCO1‐defect syndrome, " initially thought to represent a distinct disorder, indeed belongs to the genetically heterogeneous CFT dysplasia spectrum. © 2013 Wiley Periodicals, Inc.